Microplastics in Atlantic Ribbed Mussels (Geukensia demissa) from the Delaware Inland Bays, USA - Jeffrey Ashley; Amanda Pilat; Ariana Ohlweiler; Connor Ogden; Owen Bradley; Priya Modi; Spencer Talbot; Caya Smith; Justin O’Pella; Gulnihal Ozbay (Microplastics, 2024)
Due to the prevalence of plastic pollution in coastal ecosystems, aquatic organisms are at high risk for accumulating microplastics (MPs). Filter-feeding bivalves, such as mussels and oysters, may be exposed to, and subsequently accumulate, MPs due to the high volume of water they pass through their bodies. This study assessed the levels of MPs within Atlantic ribbed mussels (Geukensia demissa), a common filter feeder found along the United States Atlantic Coast, from 12 sites within Rehoboth Bay, Indian River Bay, and Little Assawoman Bay, collectively known as the Delaware Inland Bays. Composited mussels from each site were digested using potassium hydroxide and filtered. Microplastics were physically identified, sorted based on color, and counted using a digital microscope. Microplastics, almost entirely dominated by synthetic microfibers, were found in all mussels well above laboratory blanks. Across all sites, 40% of microfibers were black, and 27% of fibers were clear. The composite concentrations of MPs ranged from 0.25 to 2.06 particles/g wet tissue, with a mean of 0.08 ± 0.06. In general, higher concentrations were found in mussels collected at sites that were adjacent to more urbanized land use versus those from rural sites. At two sites, individual mussels, in addition to composites, were analyzed and had MP concentrations ranging from 11 to 69 particles/mussel. This study represents the first evaluation of MPs in this ecologically important coastal species and suggests its viability as a biomonitoring species for microplastic pollution.